Drawings in a “Container”: A Visual Narrative Approach to Research With Refugee Children - Glynis Clacherty (Social Inclusion)
Drawings can be a useful research tool as they allow children and young people to reflect on their lived experience in a form that is not dependent on words. They can, however, evoke strong memories and cause distress, particularly among children affected by war. This article describes a visual narrative approach where drawings do not exist on their own as a research tool but are embedded in an actual container, like a suitcase, or another artistic form such as a sculpture, a book, or a layered collage. The challenge this seeks to address is how to work with difficult topics in a way that allows us to apprehend the depth and complexity of the lived experience of children affected by war while protecting them from distressing memories evoked by the visual images they create. In an attempt to answer this question, the article describes a number of research encounters that have taken place over the last 15 years in eastern, central, and southern Africa in both refugee settlement and urban contexts. It explores examples of how multiple drawings are placed in a metaphorical “container” that resonates with the research purpose and the participants. The approach contains emotion, but using a multiplicity of drawings also allows children to reflect on the complexity of lives affected by war, a complexity that includes both strength and vulnerability.